551 A MULTICENTER STUDY OF RIGHT VENTRICULAR OUTFLOW TRACT TACHYCARDIA IN CHILDREN. (1st January 2006) - Harris, K. C.; Potts, J. E.; Fournier, A.; Gross, G. J.; Kantoch, M. J.; Cote, J. -M.; Sanatani, S.
Abstract : Background: Right ventricular outflow tract tachycardia (RVOT VT) in the absence of structural heart disease is considered a benign condition. As the natural history of RVOT VT in children is unknown, we sought to assess the clinical spectrum of RVOT VT and its management in children. Methods: Five participating centers identified patients for review. Patients (age ≤ 18) demonstrating VT with an inferior axis and LBBB were included. Patients with structural heart disease, myocarditis, cardiomyopathy, or long QT syndrome were excluded. Demographics, clinical presentation, investigations, and therapeutic approach were analyzed. Holter data were used to quantify ectopy. Results: Forty-eight children were included. Patients were referred for evaluation of incidental findings (39/48), near-syncope or syncope (7/48), or other (2/48). Symptoms were present in 46% of patients. Investigations included magnetic resonance imaging (51%), endomyocardial biopsy (25%), and angiography (23%). Medical treatment was initiated in 26/48. The most common indications for treatment were frequent ectopy and symptoms. Medical treatment ( p < .007) and observation alone (p < .02) were both associated with a reduction in ectopy. Symptoms persisted in 3/13 patients treated medically and all patients who had observation alone. At latest follow-up (median 21.7 months, range 1-210), there were no deaths and no difference in ectopy (p < .46) between those treated medically and those who were simply observed. Ablation was attempted in 6/48 (success in 4/6) for refractory symptoms, significant ectopy, and/or functional changes attributed to tachycardia. Conclusion: The clinical spectrum and management of RVOT VT in children are diverse. Both medical therapy and observation alone were associated with a reduction in ectopy. However, symptoms persisted in untreated patients, suggesting a possible placebo effect in the treated group.